2005
DOI: 10.1080/014850190923396
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus HPV-16 Dna as an Epitheliotropic Virus That Induces Hyperproliferation in Squamous Penile Tissue

Abstract: & The prevalence of human papillomavirus HPV-16DNA sequences in 57 penile carcinoma biopsies was examined using the polymerase chain reaction (PCR) with type specific internal probes, employing HPV consensus primers from the L1 region. The cases comprised 39 typical squamous cell carcinoma and 18 specimens with different subtype. PCR products were analyzed and HPV-16DNA was detected in a high percentage of specimens. Thirty-eight biopsies were HPV-16DNA positive. This determination was correlated with cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
0
7
2
Order By: Relevance
“…2,3,8,9,15,21,22,33,34,[38][39][40][41]47,50,52 Most reports validated the association of HPV with basaloid and warty carcinomas. 2,17,37 In some studies, about one-third of the usual and verrucous carcinomas were also reported to be positive for HPV.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…2,3,8,9,15,21,22,33,34,[38][39][40][41]47,50,52 Most reports validated the association of HPV with basaloid and warty carcinomas. 2,17,37 In some studies, about one-third of the usual and verrucous carcinomas were also reported to be positive for HPV.…”
Section: Discussionmentioning
confidence: 92%
“…1,37,44 There are many reports emphasizing the association of special subtypes of penile cancer and HPV but the prevalence figures are variable. 2,3,8,9,15,21,22,33,34,[38][39][40][41]47,50,52 The causes of these variations are not clear. They may be owing to real geographic differences in the overall incidence of HPV infection or HPV genotypes, to the use of different laboratorial techniques to detect HPV, to the original status of the paraffin blocks, to variable morphologic criteria used in the classification of penile tumors, or to other hidden reasons.…”
mentioning
confidence: 94%
“…Publications containing less than five cases were also excluded from the analysis. A final total of 31 articles were included in this review12 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 45 (see table 1). …”
Section: Methodsmentioning
confidence: 99%
“…HPV DNA has been detected in 14%–100% of invasive penile carcinomas (Bezerra et al, 2001a; Chan et al, 1994; Cupp et al, 1995; Ferreux et al, 2003; Gregoire et al, 1995; Heideman et al, 2007; Humbey et al, 2003; Iwasawa et al, 1993; Krustrup et al, 2009; Levi et al, 1998; Lont et al, 2006; Maden et al, 1993; McCance et al, 1986; Nasca et al, 1999; Pascual et al, 2007; Picconi et al, 2000; Rubin et al, 2001; Salazar et al, 2005; Sarkar et al, 1992), with higher prevalence estimates among case series with small sample sizes. Differences in methods used for DNA detection and tumor tissue storage (fresh vs. paraffin embedded) and the inclusion of tumors with different histologic subtypes may contribute to the variation in HPV prevalence across studies.…”
Section: Hpv Prevalence In Penile Cancermentioning
confidence: 99%